A Method for Cavity Scale Estimation Based on Ground-Penetrating Radar (GPR) Explorations: An Experimental Study - Jeong-Jun Park; Yoonseok Chung; Gigwon Hong (Advances in Civil Engineering)
This study described the results of experiments comparing the cavity scales obtained from the GPR exploration with the direct excavation of the identified cavity scales. The first experiment was carried out on the actual roadway, and the additional experiment was carried out on the mock-up site to prevent the cavity collapse under the ground. It was confirmed that the soil depth of the predicted cavity and the identified cavity was similar, but the predicted cavity scales by GPR exploration overestimated the longitudinal and cross-sectional widths compared with the identified cavity scales. Based on the correlation between the cavity scales predicted by GPR exploration and the cavity scales identified in the mock-up test, an empirical formula for estimating the cavity scales was proposed.